MAP4K4 Gene Silencing in Human Skeletal Muscle Prevents Tumor Necrosis Factor-α-induced Insulin Resistance - Bouzakri, Karim; Zierath, Juleen R. (The Journal of biological chemistry, 2007)
Tumor necrosis factor-α (TNF-α) induces skeletal muscle insulin resistance by impairing insulin signaling events involved in GLUT4 translocation. We tested whether mitogenic-activated protein kinase kinase kinase kinase isoform 4 (MAP4K4) causes the TNF-α-induced negative regulation of extracellular signal-regulated kinase-1/2 (ERK-1/2), c-Jun NH2-terminal kinase (JNK), and the insulin receptor substrate-1 (IRS-1) on the insulin signaling pathway governing glucose metabolism. Using small interfering RNA (siRNA) to suppress the expression of MAP4K4 protein 85% in primary human skeletal muscle cells, we provide evidence that TNF-α-induced insulin resistance on glucose uptake was completely prevented. MAP4K4 silencing inhibited TNF-α-induced negative signaling inputs by preventing excessive JNK and ERK-1/2 phosphorylation, as well as IRS-1 serine phosphorylation. These results highlight the MAPK4K4/JNK/ERK/IRS module in the negative regulation of insulin signaling to glucose transport in response to TNF-α. Depletion of MAP4K4 also prevented TNF-α-induced insulin resistance on Akt and the Akt substrate 160 (AS160), providing evidence that appropriate insulin signaling inputs for glucose metabolism were rescued. Silencing of MAP2K1 and MAP2K4, signaling proteins downstream of MAP4K4, recapitulated the effect of MAP4K4 siRNA in TNF-α-treated cells. Thus, strategies to inhibit MAP4K4 may be efficacious in the prevention of TNF-α-induced inhibitory signals that cause skeletal muscle insulin resistance on glucose metabolism in humans. Moreover, in myotubes from insulin-resistant type II diabetic patients, siRNA against MAP4K4, MAP2K4, or MAP2K1 restored insulin action on glucose uptake to levels observed in healthy subjects. Collectively, our results demonstrate that MAP4K4 silencing prevents insulin resistance in human skeletal muscle and restores appropriate signaling inputs to enhance glucose uptake.